FAKTOR YANG BERHUBUNGAN DENGAN GEJALA INTRADIALISIS PADA PASIEN HEMODIALISIS RUTIN - Antari, Gusti Ayu Ary; Widyanthari, Desak Made (Coping: Community of Publishing in Nursing, 2024)
Intradialytic symptoms  are complaints experienced by patients during hemodialysis. Although hemodialysis therapy continues to evolve, intradialytic symptoms are still frequently reported by patients, such as cramps, dizziness, headache, fatigue and others. The burden of intradialytic symptoms and prolongation of recovery time are known to have an impact on the quality of life of hemodialysis patients. Although research on intradialytic symptom management has begun, understanding the causes of intradialytic symptoms and prolonging post-hemodialysis recovery time is limited. This study aimed to identify factors associated with intradialytic symptoms. The type of research was a descriptive correlation with a cross-sectional approach. Seventy-four respondents were involved in the study and selected using purposive sampling. Intradialytic symptoms were found in 41 patients (55,4%). The average post-hemodialysis recovery time was 7,223 hours. The most common ultrafiltration rate was <10 ml/kg/hour, 47,3%. The results showed that the ultrafiltration rate had a significant association with intradialytic symptoms (p-value = 0,000). Pre-hemodialysis systolic blood pressure was not found to correlate with intradialytic symptoms. These findings have implications for improving the quality of care in the hemodialysis room by modifying risk factors to prevent the appearance of intradialytic symptoms and shorten the recovery time.